New genus and species names for the Eocene lizard Cadurcogekko rugosus Augé, 2005 - Bolet, Arnau; Daza, Juan D.; Augé, Marc; Bauer, Aaron M. (Zootaxa, 2015)
Cadurcogekko rugosus Augé, 2005 was described as a gekkotan lizard from the Eocene of France. A revision of the material has revealed that the holotype, a nearly complete dentary, actually belongs to a scincid lizard, for which we erect the new genus Gekkomimus. The rest of material originally referred to C. rugosus is of undoubted gekkotan nature and is included in the new species Cadurcogekko verus, with the exception of a partial left dentary belonging to the iguanid lizard Cadurciguana hoffstetteri.